Digital Commons for the Ecological Transition: Ethics, Praxis and Policies - Sébastien Shulz; Mathieu O’Neil; Sébastien Broca; Angela Daly (tripleC: Communication, Capitalism & Critique)
The article seeks to understand how the digital commons movement addresses ecological issues, how its actors incorporate them into their ethics and praxis, and the challenges they face in scaling up to become a viable ecological alternative to digital capitalism. Building on three case studies, we show that the digital commons currently face three major limitations: reliance on unsustainable Big Tech products, inability or unwillingness to scale up, and negligible political support. Based on two Policy Labs we conducted with actors of the digital commons movement, we conclude by outlining proposals to overcome these limits by adopting E.O. Wright’s anti-capitalist strategies framework.